Clinico-Epidemiological Study of Cutaneous Superficial Fungal Infections: Multicentre Descriptive Study - Parvaiz Anwar Rather; Mohd Rafiq Tilwani (National Journal of Medical Research)
Background: Cutaneous superficial fungal infections or dermatophytosis, have emerged as common dermatoses with increasing incidence, prevalence, and relapse rate. This study aimed to provide a comprehensive clinico-epidemiological profile of dermatophytosis in our population.